"All the Difference in the World": The Nature of Difference and Different Natures. Issue 6 (December 2020) - Heywood, Paolo
This article begins by examining the status of "difference" in representations of perspectivist cosmologies, which are themselves often represented as radically different to Euro-American cosmologies. The established reading of perspectivism emphasizes this radical difference by focusing upon the objects of difference in perspectivism (bodies, for example, rather than souls). This article experiments instead with reading perspectivism as radically resembling Euro-American thought in its conceptualization of the nature of difference, that is, the form that difference takes as a relation. It argues that in schematic representations of Amerindian and Euro-American cosmologies, difference for both is always a matter of institution and construction, and resemblance is a matter of essence and necessity. Thus, paradoxically, arguments about radical difference may in fact be read to assert an underlying essentialism as to the nature of difference itself. I conclude by proposing that we abandon conceptions of the nature of difference, in favor of a focus on "styles" of difference, and discuss some non-anthropological examples of this approach, as well as instances of different "styles" of difference from my own fieldwork.